Involvement of skeletal muscle gene regulatory network in susceptibility to wound infection following trauma. - Yiorgos Apidianakis; Michael N Mindrinos; Wenzhong Xiao; George P Tegos; Michail I Papisov; Michael R Hamblin; Ronald W Davis; Ronald G Tompkins; Laurence G Rahme (PLoS ONE)
Despite recent advances in our understanding the pathophysiology of trauma, the basis of the predisposition of trauma patients to infection remains unclear. A Drosophila melanogaster/Pseudomonas aeruginosa injury and infection model was used to identify host genetic components that contribute to the hyper-susceptibility to infection that follows severe trauma. We show that P. aeruginosa compromises skeletal muscle gene (SMG) expression at the injury site to promote infection. We demonstrate that activation of SMG structural components is under the control of cJun-N-terminal Kinase (JNK) Kinase, Hemipterous (Hep), and activation of this pathway promotes local resistance to P. aeruginosa in flies and mice. Our study links SMG expression and function to increased susceptibility to infection, and suggests that P. aeruginosa affects SMG homeostasis locally by restricting SMG expression in injured skeletal muscle tissue. Local potentiation of these host responses, and/or inhibition of their suppression by virulent P. aeruginosa cells, could lead to novel therapies that prevent or treat deleterious and potentially fatal infections in severely injured individuals.